Technology and L2 engagement in study abroad: Enabler or immersion breaker?. (February 2019) - Durbidge, Levi
Abstract: Technology has become an ever-present part of modern society, particularly in the lives of young people who make up the majority of study abroad populations. While there have been a number of studies that have looked at the role of technology in study abroad over the past few decades, they have mostly focused on tensions with the immersive aims of programs. Drawing from a larger study of adolescent study abroad, this paper reports on results which show participants using technology to engage with L2 across a range of activities during their sojourns. Analysis showed that proficiency in L2 prior to study abroad corresponded with higher rates of technology use in L2 while abroad. It also showed that there is a statistically significant relationship between some uses of technology and difficulties faced while abroad. Finally, this paper argues for a conceptualisation of technology as a feature of immersive study abroad environments and the affordances they offer for language learning and use.